A High‐Throughput Nanofluidic Device for Exosome Nanoporation to Develop Cargo Delivery Vehicles (Small 35/2021). Issue 35 (2nd September 2021) - Hao, Rui; Yu, Zitong; Du, Jing; Hu, Shi; Yuan, Chao; Guo, Hang; Zhang, Yi; Yang, Hui
Abstract : Nanofluidics In article number 2102150, Hui Yang and co‐workers report a high‐throughput nanofluidic device for loading of various cargos into exosomes. The exosomes treated by the device can deliver their drug cargos to cancer cells and induce cell death, indicating the potential opportunities of the device for developing new exosome‐based delivery vehicles for further biomedical applications.